Audit of the association between length of time spent on diagnostic work‐up and tumour stage in patients with symptomatic colon cancer. Issue 3 (4th August 2014) - Tiong, Jimmy; Gray, Andrew; Jackson, Christopher; Thompson‐Fawcett, Mark; Schultz, Michael
Abstract: Background: Colorectal cancer is one of the most incident cancers in New Zealand. Due to resource limitations, some patients experienced protracted wait times before reaching a definitive diagnosis. We analysed the relationship between time to diagnosis and clinical stage and reviewed the length of time for components of the diagnostic work‐up to identify priority areas for service improvement. We benchmarked our timeliness against introduced standards. Methods: This retrospective study included all patients with colonic (not rectal) cancer between October 2007 and September 2009. Patients were stratified into an early and advanced group. Types of delay were calculated from the onset of symptoms to the administration of treatment. The compliance with target waiting times was assessed. Results: Fifty‐eight patients were included in the early group and 83 patients in the advanced group. There were no significant differences in demographics or symptoms. The work‐up was longer than international benchmarks, but with wide variations. There was no statistical difference between lengths of work‐up in the groups. The advanced group had increased utilization of private and emergency investigations. Forty‐four per cent met the diagnostic colonoscopy target waiting time of 42 days with a trend in favour of the advanced group and 21% received treatment within 62 days (non‐significant). Conclusion: Current systems are not sophisticated enough to predict the stage of colon cancer. Here, long waiting times were not associated with cancer stage in symptomatic patients. Resources need to be directed to diagnostic colonic imaging.